Website practices of supply chain companies in Singapore - Lee, Wee Kwang. (2009)
This paper evaluates the website practices of supply chain companies in Singapore. It is achieved by first identifying appropriate website practices via thorough reviewing of literatures, and subsequently categorising these practices into three main categories: Interactional Practices, Navigational Practices and Informational Practices. This is followed by the analysis of these website practices against 1000 randomly selected websites belonging to supply chain companies in Singapore. These websites are further divided into five different supply chain industries; namely Distribution, Freight Forwarding, Logistics Services Provider, Supplier and Manufacturers. The primary objective of this paper is to find out the extend till which the websites – of each of the five supply chain industries - fare in terms of the usage of the website practices and, at the same time, to provide useful recommendations for improvement as well. Statistical tools such as one-way Analysis of Variance (ANOVA) and association rule mining technique are employed for the analysis of the website practices against the 1000 websites. One-way ANOVA was carried out using SPSS 16 while association rule mining was performed using Magnum Opus Demo. Findings resulted from both the one-way ANOVA and the association rule mining technique, have provided a vivid understanding of how the five supply chain websites fare in terms of the interactional, navigational and informational website practices. In addition, from these empirical findings, recommendations have been formulated for the supply chain industry as a whole, as well as, for each of the individual supply chain industry type. Generally, all supply chain companies in Singapore should design the News website practice along with Company Information & Products/Services Information as these three practices form the basis of an informative website. These supply chain companies, especially those with a large database of products/services information in their websites, should also realize the importance of having the Search Capability website practice. Finally, more supply chain companies should enhance their interaction with their stakeholders by including Interactive Feedback website practice into their websites.